Analisis Kerusakan Sistem Hidrolik pada Boom Silinder Unit Eskavator Komatsu PC 200-7 di PT. Wirato Mitra Mulia - Nofal Olifanta nofal; Pribadyo pribadyo; Herri Darsan (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
Boom cylinder is a component of the excavator which is located on the left and right front. This component works to move the bucket optimally by utilizing hydraulic oil flow. Boom cylinders will experience a decrease in performance if there are problems and damage to their internal parts. This Scientific Paper Analysis collects data from various direct observations in the field and makes improvements to the tools. boom cylinder malfunctions get information from the chief maintenance mechanic and experienced mechanics. This can be a basic problem of analysis, performance disturbances in the boom cylinder components can be caused by several factors, one of which is contamination that occurs in the boom cylinder. there is no inside and outside, and the occurrence of overheating in the boom part of the cylinder components. The causes of damage to the cylinder boom are very diverse, this can occur due to certain factors, including the use of the unit by the operator, steep work terrain and many other determining factors that damage the components of this cylinder boom. The problem of thinning the cylinder boom can be carried out according to procedures, capacity that is not excessive according to work standards, and daily, daily and monthly maintenance.